Speciation studies of potentially toxic elements within the vicinity of major dumpsites in Ile-Ife, Osun State, Nigeria - Oluwakemi O. Tovide; John A.O. Oyekunle; Odunayo T. Ore; Bukola A. Oyebode; Elizabeth O. Moseri; Abolanle S. Adekunle; Oluwasegun Oluwarotimi; Aderemi O. Ogunfowokan; Adebayo O. Eludoyin (Journal of Trace Elements and Minerals)
Background: This study evaluated the concentrations, speciation, and environmental risks of aluminium (Al), cadmium (Cd), manganese (Mn), lead (Pb), zinc (Zn), and copper (Cu) in the major refuse dumpsite soils of Ile-Ife, Osun State, Nigeria. Methods: Soil samples were collected from refuse dumpsite soils in Ile-Ife, Osun State, Nigeria. The soil samples were digested using HCl and HNO3 and analysed for total metal concentrations. The soil samples were equally subjected to six-step chemical fractionation protocol for speciation analysis. The metal levels were determined using Atomic Absorption Spectrophotometer. Results: The findings showed a mean distribution pattern of Mn > Zn > Cu > Pb > Cd > Al. The speciation analysis indicated that the water-soluble, exchangeable, and carbonate fractions contained more than 80 % of the metals, implying high solubility and bioavailability. The organic and residual fractions had minimal metal forms. Environmental risk assessment indices all pointed to low contamination and ecological risk, with the majority of values being less than 1. The study found that the dumpsite soils presented little environmental concern, even though metal amounts varied throughout sampling points. Conclusion: These findings emphasised that when evaluating the possible ecological effects of potentially toxic element contamination in an environment, metal speciation should be taken into account in addition to total metal concentrations so as to have a better overview of the contamination status of the environment.